Faith-Based Mentoring of Ex-Felons in Higher Education: Colson Scholars Reflect on Their Transitions - Leary, Judith A. (Religions, 2018)
This qualitative study employs the framework of Schlossberg's Transition Theory to offer readers an introduction into recently-conducted research on ex-felons transitioning into, through, and out of higher education within the context of the Colson Scholarship program at Wheaton College1, in Wheaton, Illinois. Through the material gathered from personal interviews of six completed Colson Scholars, faith-based mentors were consistently seen as significant sources of support in each stage of the college-going transition. Faith-based mentors played an important role in the outcomes of, specifically, faith-worldview development and emotional development. This article seeks to illuminate the problem of the lack of supportive mentors for ex-offender populations in our communities, and to illustrate how those mentors might be found in faith-based organizations, institutions, and houses of worship, as Johnson (Johnson 2011) asserted and also what gains could result from the involvement of faith-based mentors in the lives of correctional populations post-release.